Aeroacoustic test system design and experimental research for counter-rotating propeller - CAO Qi; WEI Kai; NIE Yanping; YAN Qun; CHEN Yonghui (Hangkong gongcheng jinzhan)
The aerodynamic noise test of counter-rotating propellers in wind tunnels has the problems of difficult time coordination and high cost. The aerodynamic noise test system of counter-rotating propellers，which is capable of simulating the driving state of counter-rotating propellers on the ground，is developed by relying on the acoustic environment of the ground. The aerodynamic noise test is carried out on a perforated counter-rotating propeller and a reference propeller to validate the test system and evaluate the noise reduction effect of the perforated counter-rotating propeller. The results show that the perforated counter-rotating propeller can effectively reduce the noise under the prerequisite of guaranteeing the aerodynamic performance in the range of the tested working conditions. In the 90° pointing angle，which has the most significant effect on the aircraft cabin，the noise reduction at the secondorder passing frequency reaches 5 dB. The designed aerodynamic noise test system can provide assistance for the evaluation of aerodynamic noise of the counter-rotating propeller and the design of noise reduction.